Coagulative behaviour of Jatropha curcas and its performance in wastewater treatment - Zainal Abidin, Zurina; Madehi, Norhafizah; Yunus, Robiah (Wiley, 2017)
Alternative natural coagulants from Jatropha curcas seed and press cake were investigated for coagulative behaviors and abilities to treat real wastewater. The characterization of the seed and press cake was done by proximate analysis while characterization on extracts which contain the active coagulant agent was conducted using FTIR, amino acid analysis, and zeta potential. The coagulation performance was evaluated using Jar Floc test on palm oil mill effluent. Proximate analysis indicated that Jatropha seed contained more protein (54%) than press cake (28%). Through HPLC analysis, 18 types of amino acid were detected in Jatropha curcas (JC) seed and press cake extracts. FTIR results confirmed the functional groups that existed in all the amino acids. The zeta potential of the extracts was positive at pH < 3 and became negative as pH increased. This means that the bio‐coagulant possessed net positive and negative charge at pH < 3 and pH > 4, respectively. Hence, the mechanism of coagulation at pH < 3 is due to adsorption and neutralization whereas at pH > 4, adsorption and interparticle bridging dominates. Dosages of 140 mg L−1 of Jatropha seed and 120 mg L−1 of press cake were required to treat 3500 NTU of POME to give 99 and 93% turbidity removal, respectively. Jatropha seed gave maximum turbidity removal at pH 3, while press cake at pH 2. The final pH of the treated POME was not altered greatly and the sludge produced was lesser in comparison to alum. In conclusion, the protein was the compound responsible for Jatropha coagulating behavior and its ability to treat real wastewater is promising.